2010
DOI: 10.1177/0146167210370032
|View full text |Cite
|
Sign up to set email alerts
|

Eye Gaze as Relational Evaluation: Averted Eye Gaze Leads to Feelings of Ostracism and Relational Devaluation

Abstract: Eye gaze is often a signal of interest and, when noticed by others, leads to mutual and directional gaze. However, averting one's eye gaze toward an individual has the potential to convey a strong interpersonal evaluation. The averting of eye gaze is the most frequently used nonverbal cue to indicate the silent treatment, a form of ostracism. The authors argue that eye gaze can signal the relational value felt toward another person. In three studies, participants visualized interacting with an individual displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
225
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(244 citation statements)
references
References 54 publications
13
225
2
4
Order By: Relevance
“…This resulted in a sample of 121: 70 students from a German university (57 female and 13 male) and 51 students from a Turkish university (44 2 In our calculations, we averaged all basic needs items together to create an overall measure of basic need satisfaction as all needs were highly intercorrelated, rs > .48, ps < .001. We used this procedure in alignment with recent social exclusion research (e.g., Wirth, Sacco, Hugenberg, & Williams, 2010 …”
Section: Methods Participantsmentioning
confidence: 99%
“…This resulted in a sample of 121: 70 students from a German university (57 female and 13 male) and 51 students from a Turkish university (44 2 In our calculations, we averaged all basic needs items together to create an overall measure of basic need satisfaction as all needs were highly intercorrelated, rs > .48, ps < .001. We used this procedure in alignment with recent social exclusion research (e.g., Wirth, Sacco, Hugenberg, & Williams, 2010 …”
Section: Methods Participantsmentioning
confidence: 99%
“…For example, the eyes contain information that allows us to better identify and recognize specific individuals (McKelvie, 1976). They also provide valuable information about the direction of a person's visual attention which has critical implications for understanding intentions, preferences, and approach-avoidance behaviors (Adams & Kleck, 2003Hietanen, Leppänen, Peltola, Linna-Aho, & Ruuhiala, 2008;Itier & Batty, 2009;Mason, Hood, & Macrae, 2004;Mason, Tatkow, & Macrae, 2005).The above research indicates that attending to the eyes can help us form impressions and regulate social interactions (Frischen, Bayliss, & Tipper, 2007;Kleinke, 1986;Nummenmaa, Hyönä, & Heitanen, 2009;Richmond, McCroskey, & Hickson, 2007;Wirth, Sacco, Hugenberg, & Williams, 2010). Recent work, however, has also demonstrated that individuals who do not preferentially attend to others' faces and eyes commonly experience social (Yardley, McDermott, Pisarski, Duchaine, & Nakayama, 2008) and developmental deficits (Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001;Baron-Cohen, Wheelwright, & Jolliffe, 1997).…”
mentioning
confidence: 99%
“…Interestingly, a relatively small number of studies investigated attentional deployment in response to social feedback. Within the social (rejection) context, prior eyetracking studies have mainly investigated averted/directed eye gaze as a nonverbal form of ostracism (e.g., Wirth, Sacco, Hugenberg, & Williams, 2010) or to emotional faces after (threat of) social exclusion (e.g., DeWall, Maner, & Rouby, 2009). Silk and colleagues (2012) investigated visual gazes during a naturalistic viewing condition after being included or excluded from a chat game, specifically focusing on the attentional allocation towards self-relevant information.…”
mentioning
confidence: 99%